A medieval site at Børvågneset: Arkeologisk undersøking på Andøya i Nordland - Kvalheim, Alice Sunde (Tromura, 2026)
In the summer of 2025, we excavated a burrow located at Børvågneset in Andøy kommune. The burrow had been dated to the Middle Ages during the registration work, and our examinations confirmed this. The area also yielded several dates ranging from the 16th century all the way up to the 19th century. This provides evidence of long and continuous use of the area. In more recent times, the site is known as a harbor for fishing activities.The burrow itself offered very few clues about its construction—no construction elements were recorded except for an intentionally dug pit. A small layer of coal inside the pit provided a C-14 date of 1274–1299 A.D.
Keywords: Archaeological excavation; Middle Ages; Fishery; House Foundation; Northern Norway